Recent Advances in the Synthesis and Biomedical Applications of Nanocomposite Hydrogels - Umile Gianfranco Spizzirri; Manuela Curcio; Giuseppe Cirillo; Tania Spataro; Orazio Vittorio; Nevio Picci; Silke Hampel; Francesca Iemma; Fiore Pasquale Nicoletta (MDPI AG, 2015)
Hydrogels sensitive to electric current are usually made of polyelectrolytes and undergo erosion, swelling, de-swelling or bending in the presence of an applied electric field. The electrical conductivity of many polymeric materials used for the fabrication of biomedical devices is not high enough to achieve an effective modulation of the functional properties, and thus, the incorporation of conducting materials (e.g., carbon nanotubes and nanographene oxide) was proposed as a valuable approach to overcome this limitation. By coupling the biological and chemical features of both natural and synthetic polymers with the favourable properties of carbon nanostructures (e.g., cellular uptake, electromagnetic and magnetic behaviour), it is possible to produce highly versatile and effective nanocomposite materials. In the present review, the recent advances in the synthesis and biomedical applications of electro-responsive nanocomposite hydrogels are discussed.